Analysis of the Influence of the Level of Implementation of the Occupational Safety and Health Management System (SMK3) on the Accident Rate in Housing Projects - Adha, Muhammad Fajar; Suroso, Agus (Universitas Ibn Khaldun Bogor, 2025)
The so-called Occupational Safety and Health Management System (SMK3) is part of the overall management system which includes organizational structure, planning, responsibilities, implementation, procedures, processes, and resources needed for the development, implementation, achievement, review, and maintenance of K3 policy in the context of controlling work-related risks to create a safe, efficient and timely workplace. An accident is an unexpected event that results in serious injury or illness to an employee and can result in property damage. The aim of this research, based on the background and problem formulation above, is to determine the factors that influence the Occupational Safety and Health Management System (SMK3) in Housing Development projects and to analyze the factors that significantly influence the Occupational Safety and Health Management System (SMK3) on Housing Development projects. The methods used are surveys, interviews, and data analysis in the field. The identified SMK3 risk factors include non-compliance with work safety procedures, lack of SMK3 training or certification for workers, unsafe work environment conditions, use of unsafe equipment or machines, inaccuracy or negligence of workers, and lack of personal protection or adequate safety equipment. To overcome this risk, strict and appropriate SMK3 standards are needed. Safety regulations not implemented in the project environment make the level of health and safety fall into the low category. Jobs that are at risk of causing work accidents.